Native Landscape Plants for South Florida - Jody Haynes; John McLaughlin; Laura Vasquez (EDIS)
A previous publication, ENH854 (http://edis.ifas.ufl.edu/EP107), listed over 350 native and non-native plant species for south Florida. This new publication was developed as a supplement to ENH854, but it is also a good stand-alone reference for people wishing to add native plants to their private yards or public landscapes, or simply to learn more about them. This document is ENH 875, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 29, 2003.